PENGARUH MODEL PROBLEM SOLVING DENGAN MENGGUNAKAN METODE BRAINSTROMING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMP NEGERI 2 LUBUKLINGGAU - Ulandari, Tipa; sukasno, sukasno; Purwasi, Lucy Asri (Jurnal Pendidikan Matematika Undiksha, 2020)
ABSTRACTÂ This thesis is entitled "The Effect of Problem Solving Learning Model Using Brainstroming Methods Against the Mathematical Problem Solving Ability of Class VII Students of SMP Negeri 2 Lubuklinggau". This study aims to determine whether there is an effect of the Problem Solving Learning Model by using the Brainstroming Method to the Mathematical Problem Solving Ability of Class VII Students of SMP Negeri 2 Lubuklinggau. This type of research is in the form of Experimental Design Tru. The population, all students of class VII of SMP Negeri 2 Lubuklinggau were 406 students and the sample was class VII.5 with 35 students as experimental class and VII.4 with 35 students as control class. Sampling is done randomly. Data collection in research using test techniques. The collected data were analyzed using t-test at a significant level Î± = 0.05. Based on the results of data analysis, it can be concluded that There is an Effect of Problem Solving Learning Model by Using Brainstroming Method to the Mathematical Problem Solving Ability of Class VII Students of SMP Negeri 2 Lubuklinggau. The average value of the problem solving ability of the experimental class was 62.5 and the control class was 43.3.